2017
DOI: 10.1111/trf.14182
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plerixafor on the mobilization of CD34+ cell subpopulations and lymphocyte subtypes

Abstract: In contrast to the findings of other authors, our study shows a clear shift toward more committed CD34+ subsets after plerixafor in poor mobilizers and elucidates the importance of informative surface markers like CD45RA and CD133 in addition to CD38 to discriminate earlier from more committed CD34+ cells. Further studies are needed to analyze whether these findings have an impact on clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Only 0.2–2.8% of CD34 + cells were CD38-negative, but this may be consistent with plerixafor’s effect in normal healthy donors, in that fewer HPC may be mobilized by plerixafor than by G-CSF, where up to 50% of G-CSF-mobilized CD34 + cells are CD38-negative. 13 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…Only 0.2–2.8% of CD34 + cells were CD38-negative, but this may be consistent with plerixafor’s effect in normal healthy donors, in that fewer HPC may be mobilized by plerixafor than by G-CSF, where up to 50% of G-CSF-mobilized CD34 + cells are CD38-negative. 13 , 40 …”
Section: Discussionmentioning
confidence: 99%
“…Based on this observation and previous reports, possibly the peak of CD34+ cells could occur later. A study by Worel et al indicated a high-committed cell population in graft after plerixafor mobilization at 6 -12 hours' time interval (33). On the contrary, Shi et al suggested that despite CD34+ cells peak after 12 hours, CD38-/CD34+ cells, with higher priority, reach their peak between 10 and 18 hours (34).…”
Section: Discussionmentioning
confidence: 99%
“…Different administration schedules could advantageously be studied in order to perhaps optimize mobilization of TCR γδ and NK cells. Moreover, the effects on TCR γδ and NK cell of another mobilizing agent, Plerixafor, are unknown and as this information could also help guide decisions on different mobilization strategies ( 41 , 42 ).…”
Section: Discussionmentioning
confidence: 99%